Soil physical properties under different uses in the coastal tableland’s region of Espírito Santo - Piassi, Juliana Zambom; Jorge, Jessica Almeida; Nardotto Júnior, André Orlandi; Nascimento, Adriel Lima; Lira, Rickelme Zordan de; Taliaferro, Tiago Marcarini; Gonçalves, Eduardo Cosme; Silva, Francine Bonomo Crispim; Bonomo, Robson; Gontijo, Ivoney; Pires, Fabio Ribeiro (Brazilian Journal of Production Engineering, 2025)
Monitoring soil quality through its physical properties is important for diagnosing and maintaining the sustainability of agricultural systems. Physical indicators are related to the arrangement of particles and pores, affecting root development, seedling emergence and water infiltration. The aim was to evaluate changes in the physical properties of the soil in the Tabuleiros Costeiros region of São Mateus-ES, under the cultivation of perennial crops, providing relevant information for the management of these agricultural systems. The study was carried out on Yellow Argissolo in a completely randomized experimental design (DIC), in a 3x2 factorial scheme, with three adjacent areas (black pepper, coco-da-baía and native forest), at two depths (0-20 and 20-40 cm) and five replications. Soil resistance to penetration, moisture, macro and microporosity, soil density, aggregate stability and organic matter were evaluated. The native forest showed more favorable results for plant development. The cultivated areas showed differences in the properties evaluated, with dissimilarity in relation to the forest and similarity between them, for both depths. The replacement of native vegetation caused an increase in soil density and a reduction in microporosity, total porosity, organic matter and aggregate stability, showing the effect of conventional soil cultivation on its physical attributes.